Meta Analisis Model Pembelajaran Kooperatif Tipe Group Investigation Terrhadap Hasil Belajar Fisika Siswa Di SMA - Helma Ariani Hasibuan; Putri Rahayu; Putri Roma Uly Nyata Sihombing; Siti Kholija Nasution (Jurnal Bintang Pendidikan Indonesia, 2024)
This research takes the form of a meta-analysis aiming to encompass findings regarding the influence of the cooperative learning model called Group Investigation (GI) on high school students' physics learning outcomes. It aims to identify the independent variable, which is cooperative learning, and the dependent variable, which is high school students' physics learning outcomes. The study includes 20 journal articles on the Group Investigation cooperative learning model that align with the research objectives. The average effect size calculation resulted in an average effect size of 0.86. The average effect size based on the learning outcomes of the Group Investigation type was 0.80. It was observed that the highest level based on the class level was achieved in Grade XI with an effect size of 0.97, while Grade X also attained a high effect size. This demonstrates the effectiveness of the Group Investigation cooperative learning model, especially in Grade XI of high school. The overall percentage of journal articles categorized by effect size is as follows: high impact category 20%, very high impact category 10%, high category 20%, moderate category 30%, and finally, a small impact category with 20%. From the analysis, it's evident that journals on the Group Investigation cooperative learning model are highly relevant for use in the learning process due to their influence on students' physics learning outcomes in high school.